1993
DOI: 10.1042/bj2930207
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine nucleotide metabolism in rat hepatocytes: evidence for compartmentation of nucleotide pools

Abstract: Pyrimidine nucleotide metabolism in rat hepatocytes was studied by measurement of the labelling kinetics of the various intermediates after double labelling with [14C]orotic acid and [3H]cytidine, the precursors for the de novo and the salvage pathways respectively. For the uridine nucleotides, differences were found for the 14C/3H ratios in the UDP-sugars, in UMP (of RNA) and in their precursor UTP, suggesting the existence of separated flows of the radioactive precursors through the de novo and the salvage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…For UTP and the other uridine derivatives studied, this increase was much more pronounced than for the cytidine derivatives, irrespective of the use of either uridine or cytidine. This is in agreement with previous observations (Pels Rijcken et al, 1993). It shows that the synthesis of CTP is strictly regulated, probably by feedback inhibition.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…For UTP and the other uridine derivatives studied, this increase was much more pronounced than for the cytidine derivatives, irrespective of the use of either uridine or cytidine. This is in agreement with previous observations (Pels Rijcken et al, 1993). It shows that the synthesis of CTP is strictly regulated, probably by feedback inhibition.…”
Section: Resultssupporting
confidence: 94%
“…As part of our studies [see also Pels Rijcken et al (1990, 1993] processed during the subsequent transport to their final deson the latter mode of regulation, we determined the effect of tination. This process has appeared to be an essential prerequisite increases of the nucleotide-sugar pools in rat hepatocytes, as for obtaining biologically competent molecules at their proper brought about by pretreatment of the cells with uridine and location (Lodish, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, with respect to the analysis of CHO cell extracts, similar proportions of nucleotide-sugars were reported to occur in rat hepatocytes. Pels Rijcken et al (1993) reported high concentrations of UDP-sugars (e.g., 2.96 nmol UDP-HexNAc/10 6 cells, 3.95 nmol UDP-Hex/10 6 cells) relative to CMP-Nacetylneuraminic acid (CMP-NeuAc) content (0.24 nmol/ 10 6 cells). It is interesting to compare the cellular content of nucleotide sugar substrates with that of the recombinant IFN-␥ glycoprotein.…”
Section: Discussionmentioning
confidence: 98%
“…Endogenous nucleotides are recycled intracellularly (25,26) and intracellular metabolic activities appear to be compartmentalised (27) in a way which allows incoming exogenous precursors to be catabolised and replaced in a single hepatic transit by salvageable products of de novo synthesis (28). Most incoming nucleosides in portal venous blood are removed in a single passage (29,30).…”
Section: Role Of the Liver In Nucleotide Homeostasis In Vivomentioning
confidence: 99%